A conspiracy of silence: subsistence hunting rights in the Brazilian Amazon - (:unkn) unknown (Museu Paraense Emílio Goeldi, 2019)
Subsistence hunting is an important cultural activity and a major source of dietary protein and other products for indigenous and non-indigenous populations throughout the Amazon. However, subsistence hunting has an uncertain legal status in Brazil, leaving many traditional and rural Amazonian populations subject to arbitrary interpretation and contradictory application of laws. The 1967 Wildlife Protection Act, which helped curb the killing of wild animals for the international leather market, made hunting of all wild animals illegal. Subsequently, only indigenous peoples had their hunting rights explicitly recognized in Brazilian law. Exceptions for other traditional and rural populations were then introduced, allowing subsistence hunters to own and license firearms and to hunt with them in a “state of necessity” or “to satisfy hunger,” through the Brazilian Disarmament Statute and the Environmental Crimes Act.
Uma conspiração de silêncio: direitos de caça de subsistência na Amazônia brasileira
Keywords: Segurança e soberania alimentar; Direitos indígenas; Direitos dos povos tradicionais; Legislação ambiental brasileira; Reservas de uso sustentável; Terras indígenas; CNPQ::CIENCIAS HUMANAS